Reformation fictions: polemical Protestant dialogues in Elizabethan England - Zlatar, Antoinina Bevan (Oxford University Press, 2011)
'Reformation Fictions' rehabilitates a body of little-known Elizabethan texts. It takes some twenty polemical Protestant dialogues written predominantly by puritan clerics and, for the first time, gives them a literary, historicist and, to a lesser extent, theological reading